Functional changes during hospital stay in older patients admitted to an acute care ward: a multicenter observational study. - Stefanie L De Buyser (PLoS ONE, 2014)
Objectives Changes in physical performance during hospital stay have rarely been evaluated. In this study, we examined functional changes during hospital stay by assessing both physical performance and activities of daily living. Additionally, we investigated characteristics of older patients associated with meaningful in-hospital improvement in physical performance. Methods The CRiteria to assess appropriate Medication use among Elderly complex patients project recruited 1123 patients aged ≥65 years, consecutively admitted to geriatric or internal medicine acute care wards of seven Italian hospitals. We analyzed data from 639 participating participants with a Mini Mental State Examination score ≥18/30. Physical performance was assessed by walking speed and grip strength, and functional status by activities of daily living at hospital admission and at discharge. Meaningful improvement was defined as a measured change of at least 1 standard deviation. Multivariable logistic regression models predicting meaningful improvement, included age, gender, type of admission (through emergency room or elective), and physical performance at admission. Results Mean age of the study participants was 79 years (range 65-98), 52% were female. Overall, mean walking speed and grip strength performance improved during hospital stay (walking speed improvement: 0.04±0.20 m/s, p<0.001; grip strength improvement: 0.43±5.66 kg, p = 0.001), no significant change was observed in activities of daily living. Patients with poor physical performance at admission had higher odds for in-hospital improvement. Conclusion Overall, physical performance measurements show an improvement during hospital stay. The margin for meaningful functional improvement is larger in patients with poor physical function at admission. Nevertheless, most of these patients continue to have poor performance at discharge.